Collaborative Response to Intervention Strategies for Dyslexic Junior High School Students: Strategi Response to Intervention Kolaboratif untuk Siswa Disleksia Sekolah Menengah Pertama - Rahmawati Rahmawati; Iis Prasetyo (Academia Open, 2026)
General Background Inclusive education systems must provide equitable learning opportunities and specialized support for learners with specific learning disabilities. Specific Background At SMP Negeri 3 Teluk Pandan, learners with dyslexia face persistent reading, spelling, and comprehension challenges without systematic early identification or structured individualized assistance. Knowledge Gap While tiered learning frameworks exist, the practical integration of structured multi-tier instructional models with organized educator-family partnerships within Indonesian secondary education settings remains underexplored. Aims This study investigates the application of a tiered instructional framework and the role of educator-family partnerships in supporting the academic activities of learners facing literacy challenges. Results Utilizing a qualitative case study design, the analysis revealed that tiered instructional delivery—ranging from universal classroom accommodations to intensive individualized support—promoted reading fluency, comprehension, and self-confidence. Collaborative planning and home-based reinforcement sustained these academic gains, despite institutional constraints such as limited instructional time, varying parental capacity, and heavy teaching workloads. Novelty This research specifically isolates the synergistic mechanism between school-based tiered accommodations and home-based parental reinforcement in diagnosing and addressing secondary education literacy deficits. Implications Educational institutions must institutionalize systematic screening protocols and dedicate resources for cross-stakeholder communication to ensure sustainable, adaptive, and inclusive learning environments for populations facing literacy disorders. Highlights Tiered instructional delivery progressed reading fluency, text comprehension, and learner self-confidence. Active partnerships between educators and families successfully reinforced academic gains through consistent home-based practice. Institutional constraints, including limited teaching time and varying guardian capacity, challenged the continuous application of personalized assistance. Keywords Inclusive Education; Tiered Instructional Delivery; Reading Fluency; Educator-Family Partnerships; Literacy Deficits